The Use of Traditional Forms of Communication for Honey Gathering in Rural Sri Lanka - Thushari Madhubhashini Galagedarage (International Journal of Media and Communication Research, 2021)
The different forms of traditional communication are used in honey gathering at the local and international levels. Therefore, the main purpose of the study is to examine the use of traditional forms of communication in traditional honey gathering in Sri Lanka. Development communication is the main conceptual and theoretical framework of the study. The geographical location is Anuradhapura district, North Central Province in Sri Lanka. The study used a qualitative approach to obtain data using the in-depth interview method. The qualitative data were analyzed thematically. The results show that, the different traditional forms of communication such as natural smokes, Kem Krama (kind of ritual treatments), rite and rituals, folk tales, folk poems, folk ceremonies etc. are used to reach the honey hive and inactivate the bees without killing or harming, to cut honey combs and to collect honey carefully and cautiously. The most important thing is that the responsible authorizes should also take necessary actions to empower traditional honey collectors to maintain the traditional honey gathering. Combing traditional folk communications and modern techniques, safety measures and educating honey collectors to avoid the potential risks are some of the solutions to increase the honey harvest as well as to empower the honey collectors who engage in this profession. Keywords: Traditional forms of communication; Folk media; honey gathering; rural; Sri Lanka